Experimenting over a Long Distance: A method to facilitate intercultural experiments - Gari Walkowitz; Clemens Oberhammer; Heike Henning-Schmidt (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
We report a new method for Experimenting over a Long Distance (ELD)allowing to simultaneously run decentralized interactive experiments in geographically separated subject pools. Applying ELD to an intercultural trust experiment with participants from Argentina, China and Germany we found a striking evidence for transcontinental trust behavior. In addition to Chinese senders' discrimination of Argentinean players no discrimination in trust and reciprocity behavior was observed. Neverthe- less, we found significantly different levels of trust and reciprocity in the different national cultures.
Keywords: O57; F00; C91; C81; C72; 330; interactive intercultural experiments; investment game; trust